Children born of war
1 online resource.
Keywords: "This volume presents research from a European international, interdisciplinary and intersectoral research project in which fifteen doctoral researchers explored a range of issues related to the life-course experiences of children born of war in 20th-century conflicts. It explores methodological and ethical issues related to research with war-affected populations in general and children born of war in particular, presents innovative historical research focussing specifically on geopolitical areas that have hitherto been unexplored, addresses, from a psychological and psychiatric perspective, the challenges faced by children born of war in post-conflict communities"--